Development and validation of a physical activity-sleep-academic performance model for students - Zhanguo Su; Yiping Su; Junyan Meng (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Student well-being is increasingly at risk due to sedentary behavior, sleep deprivation, and academic stress. These issues are interrelated and influenced by both personal habits and environmental contexts.